A Case of Neonatal Marfan Syndrome: A Management Conundrum and the Role of a Multidisciplinary Team - Elliott J. Carande; Samuel J. Bilton; Satish Adwani (Case Reports in Pediatrics)
Neonatal Marfan syndrome (nMFS) is a rare condition with a poor prognosis. It is genotypically and phenotypically distinct from the typical Marfan syndrome and carries a poorer prognosis. This case report describes the progression of a 14-month-old girl diagnosed with nMFS at 5 months of age. Her diagnosis followed the identification of a fibrillin-1 mutation (FBN1 gene, exon 26, chromosome 15), which is a common locus of nMFS. This patient developed severe cardiac complications resulting in congestive cardiac failure in early life and required major cardiac surgery. Since surgical intervention, our patient is still reliant on a degree of ventilator support, but the patient has gained weight and echocardiography has demonstrated improved left ventricular function and improved tricuspid and mitral valve regurgitation. Therefore, we argue the importance of a cautious multidisciplinary approach to early surgical intervention in cases of nMFS.